Optimasi Ekstraksi Isolat Protein Jewawut dengan Metode Ultrasonic Assisted Extraction - Al Islamiyah, Syahmidarni; Tiffany, Margaretha H (Universitas Pattimura, 2025)
The demand for protein from plant sources is increasing in line with the clean label trend. Emulsifiers often originate from synthetic or animal sources, which are less suitable for this trend; hence, plant-based emulsifiers have emerged as a promising solution. The aim of this research was to optimize the extraction of millet protein isolate, characterize the physicochemical properties of the produced isolate, and compare it with other emulsifiers. The extraction method employed Ultrasonic-Assisted Extraction and utilized a Response Surface Methodology optimization design based on a central composite design model. The research variables consisted of the solvent-to-sample weight ratio and extraction time, with the emulsion activity index (EAI) and emulsion stability index (ESI) as response variables. Other test parameters included oil absorption capacity, water absorption capacity, yield, and crude protein content. The results showed that the emulsion activity index increased as the solvent:sample weight ratio increased, as indicated by a positive regression coefficient. However, it decreased with longer extraction time, as indicated by a negative regression coefficient. Meanwhile, the emulsion stability index will increase with both higher solvent:sample weight ratios and longer extraction times, as indicated by a positive regression coefficient. The optimal extraction condition was obtained at solvent to sample of ratio (1:35) and extraction time of 22,15 minutes, resulting in a yield of 85,25%, EAI of 402,67 m²/g, ESI of 1508,45 minutes, an oil absorption capacity of 1,56 g/g, a water absorption capacity of 1,02 g/g, and a crude protein content 17,35% (dry weight). Compared to the gum arabic, the produced millet protein isolate exhibited better characteristics across all tested parameters.